PREVALENCE AND CHARACTERISTIC OF REFRACTIVE ERRORS IN ADOLESCENT CHILDREN AT SMP NEGERI 3 DENPASAR IN 2021 - Arianingtyas, Ni Made Dwitya; Triningrat, Anak Agung Mas Putrawati; Utari, Ni Made Laksmi; Sutyawan, I Wayan Eka (E-Jurnal Medika Udayana; Vol 11 No 11 (2022): E-Jurnal Medika Udayana, 2022)
Refractive error is a condition in which a firm image is not formed on teh retina but on the front or back of the yellow spot and is not located at a sharp poiyn. There are three refractive errors, namely myopia, hypermetropia, astigmatism or a mixture of these disorders. Among these refractive errors, myopia is the most common. The purposes of this study was to find study was to find out how the prevalence and characteristik of refractive errors in adolescent children at SMP Negeri 3 Denpasar in 2021. The design of this study used a cross sectional method where the sample collection in this study was conducted non-randomly (non-probability sampling) with purposive technique sampling. Data analysis was carried out descriptively by looking at the percentageand frequency values. In this study, as many as 232 students filled out the questionnaire, but only 46 studentd uses glasses. The characteristics of adolescents with refractive error at SMP Negeri 3 Denpasar were 36 children (78.3%) aged 14 years, which weredominated by women as many as 27 children (58.7%). In children, refractive errors are more common in the growth period where increased activity coincides with increased eye activity through near vision activities. The conclusion of this study is that the prevalence of the use of glasses in adolescents with refractive errors at SMP Negeri 3 Denpasar is 46 children (19.8%) of the 232 adolescent students who filled out the questionnaire.